These are the Days of Haggai and Zechariah: The Literary Function of the Prophets in Ezra 1-6 - Lortie, Richard Christopher (My University, 2008)
The scholarly conversation concerning Ezra-Nehemiah has largely been focussed on diachronic methods. Tamara Eskenazi was the first to consider Ezra-Nehemiah synchronically. Her work was an exceptional as well as essential step forward. However, her focus on the unity of Ezra and Nehemiah causes her to overlook the plot structure of Ezra 1-6. In this study a plot structure is outlined for Ezra 1-6 based upon the עלה imperative and the בנה imperative which are given by Cyrus in Ezra 1 :2-4. The Judean people are able to accomplish the עלה imperative without conflict, but the בנה imperative is not completed so easily as the temple rebuilding project reaches a standstill in Ezra 4:24. The prophets Haggai and Zechariah then intervene and become the catalyst for the resolution ofthe narrative (5:1). This study highlights the narrative role of the prophets in Ezra 1-6.
Keywords: Religion; Religion